Vulvodynia - still a challenging therapeutic problem - Magdalena Pawlaczyk; Katarzyna Korzeniowska; Mariola Pawlaczyk (Termedia Publishing House, 2017)
Introduction . Vulvodynia is a chronic condition characterized by pain and burning in the vulvar area without any abnormalities in clinical and laboratory examinations. The diagnosis is based on detailed assessment of medical history, physical examination and exclusion of other potential causes of vulvar pain. As yet, no definitive treatment algorithm has been universally accepted for vulvodynia. Objective . To present a case of successful treatment of generalized spontaneous vulvodynia with low doses of amitriptyline. Case report . A 42-year-old patient presented to a dermatology outpatient clinic with chronic generalized vulvar pain of 2 years' duration. She was diagnosed with generalized spontaneous vulvodynia. Amitriptyline treatment was introduced and supported by topical application of lignocaine gel. After 13 months of amitriptyline therapy a complete remission was achieved. Conclusions . Vulvodynia is a complex disease with numerous presentations, the symptoms of which often overlap. Since the diagnosis of vulvodynia requires the exclusion of other abnormalities, it is fundamental to raise the awareness of the disease among clinicians, so as to enable early correct diagnosis and adequate treatment.